THE IMPLEMENTATION OF INFORMATION GAP ACTIVITIES TO IMPROVE STUDENTSâ SPEAKING AND READING SKILLS - Abduh, Nurdevi Bte (Lembaga Perpustakaan Unismuh Makassar, 2013)
This study was conducted to know whether or not the use of Information Gap activities improves studentsâ accuracy in speaking skill that cover three elements of accuracy; vocabulary, pronunciation, and grammar; and to know whether or not the use of Information Gap activities improves studentsâ literal comprehension in reading skill. This research applied a quasi experimental design; the non equivalent control group design. It used two groups; experimental groups and control group. The data obtained from the test was analyzed quantitatively and then itsâ result was compared with t-table to know whether they were significantly different or not. The data showed studentsâ mean score of accuracy in speaking skill and literal comprehension in reading skill improved after teaching by using Information Gap activities. In experimental class, the studentsâ accuracy of pretest was 1.55 and improved to be 3.06 in posttest, studentsâ literal comprehension of pretest was 0.82 and posttest was 3.21. In control class, the studentsâ accuracy was 1.90 for pretest and 2.32 for posttest; studentsâ literal comprehension was 1.63 for pretest 2.27.Â These findings indicate that the mean score of posttest was greater than pretest for that both class. However, the studentsâ mean score in experimental was greater than control class where accuracy (3.06>2.37) and literal comprehension (3.21>2.27). It meant that implementing Information Gap activities were effective to improve the studentsâ speaking and reading skills.Keywords: Speaking and reading skills, accuracy, literal comprehension, Information Gap ActivitiesPenelitian ini dilakukan untuk mengetahui apakah penggunaan kegiatan Informasi Gap meningkatkan akurasi siswa dalam keterampilan yang mencakup tiga unsur akurasi berbicara; kosakata, pengucapan, dan tata bahasa; dan untuk mengetahui apakah penggunaan kegiatan Informasi Gap meningkatkan pemahaman literal siswa dalam keterampilan membaca. Penelitian ini menerapkan desain kuasi eksperimental; desain kelompok kontrol non setara. Ini digunakan dua kelompok; kelompok eksperimen dan kelompok kontrol. Data yang diperoleh dari tes dianalisis secara kuantitatif dan kemudian hasilnya dibandingkan dengan t-tabel untuk mengetahui apakah mereka berbeda secara signifikan atau tidak. Data menunjukkan akurasi nilai rata-rata siswa dalam keterampilan dan pemahaman literal berbicara dalam keterampilan membaca membaik setelah mengajar dengan menggunakan kegiatan Informasi Gap. Di kelas eksperimen, akurasi siswa pretest adalah 1,55 dan ditingkatkan menjadi 3,06 di posttest, pemahaman literal siswa dari pretest adalah 0,82 dan posttest adalah 3,21. Di kelas kontrol, akurasi siswa adalah 1,90 untuk pretest dan untuk posttest 2,32; pemahaman literal siswa adalah 1,63 untuk pretest 2,27. Temuan ini menunjukkan bahwa nilai rata-rata dari posttest lebih besar dari pretest untuk kedua kelas. Namun, nilai rata-rata siswa dalam eksperimen lebih besar dari kelas kontrol di mana akurasi (3,06> 2,37) dan pemahaman literal (3.21> 2.27). Ini berarti bahwa pelaksanaan kegiatan Informasi Gap yang efektif untuk meningkatkan berbicara dan membaca keterampilan siswa.Kata Kunci: Berbicara dan keterampilan membaca, akurasi, pemahaman literal, Informasi Gap Aktivitas.